Manajemen Pemeliharaan dan Risiko Infestasi Nematoda Gastrointestinal pada Sapi di Wilayah Berbeda - Zulfikar Zulfikar; Sayed Umar; T. Reza Farasyi; Ma'ruf Tafsin (Jurnal Serambi Engineering, 2022)
The study was conducted to identify rearing management so that there is an increased risk of gastrointestinal nematode infestations in cattle in different areas. Pidie Jaya Regency represents the lowlands and Bener Meriah Regency represents the highlands. The number of samples of respondents is 52 people, consisting of 28 respondents in the lowlands and 24 respondents in the highlands who were given a questionnaire related to the production mechanism, health and environmental management of cattle. Formulation of the data is done by the Odds Ratio (OR) test, followed by the Chi-square and P-value tests. The results of the assessment of the production mechanism showed that cattle were more at risk of infesting in the lowlands (Pidie Jaya) than in the highlands (Bener Meriah) and there was a significant difference (P0.05). For health management, it can be seen that the behavior of respondents in handling health is worse in the lowlands (Pidie Jaya) than in the highlands (Bener Meriah) and there is a significant difference (P0.05). For environmental knowledge that affects the high gastrointestinal nematode infestation in cattle, it can be seen that between the lowland region (Pidie Jaya) and the highland region (Bener Meriah) there is no significant difference (P0.05) both are still low in knowledge. With appropriate maintenance management (production, health and environment), it is very supportive for the sustainability of production and productivity of a farm, including the raising of cattle.